Structure, activity, and drug-likeness of pure compounds of Sumatran lichen (Stereocaulon halei) for the targeted ACE2 protein in COVID-19 disease - Purnawan Pontana Putra; Surya Sumantri Abdullah; Risma Rahmatunisa; Junaidin Junaidin; Friardi Ismed (Universitas Ahmad Dahlan, 2020)
Sumatran lichen has the potential as antiviral, pure isolates that have been isolated and developed as prospective compounds for COVID-19 treatment. Computational methods were used to accelerate the discovery and screening of potential new compounds. The molecular structures of the isolated compounds such as Lobarin, Atranorin, Methyl 2,4-dihydroxy-3,6-dimethylbenzoate, Methyl 3â€formylâ€2,4â€dihydroxyâ€6â€methylbenzoate, Ethyl 3-formyl-2,4-dihydroxy-6-methylbenzoate, and Lobaric acid were drawn, then their activities were analyzed, processed by docking with ACE2 protein, and tested for Druglikeness. The activities and druglikeness were determined in the Swiss ADME program, while the ACE2 docking was processed by Blind Docking in Arguslab, AutoDock Vina, Open Babel, and Discovery Studio Visualizer programs. All compounds bound to the ACE2 protein, as apparent from the number of hydrogen bonds between the two. The Gibbs free energy was in the range of -5.6 to -7.0, and the best one was obtained from atranorin. As for lobarin, this compound was found to be non-drug-like.